Terapi Akupresur pada Pasien Paska CABG - Kurnia, Pasti; Herawati, Tuti; Maria, Riri; Waluyo, Agung (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effect of acupressure therapy on patients who experience various complaints of nausea, vomiting, pain, sleep disorders, constipation, and anxiety after cardiac surgery. The method used is searching for several sources using Scoping Review using the PRISMA flow diagram, searching for sources from PubMed, EMBASE, Science Direct, and Scopus. The research results showed that ten articles reviewed the effects of acupressure therapy after CABG heart surgery, such as nausea, vomiting, pain, sleep disorders, constipation, and anxiety. In conclusion, acupressure intervention can be applied to reduce various complaints after CABG heart surgery at the Neiguan (PC6), Shenmen (HT7), Fengchi (GB20), Jiache (ST6), Yintang (EX-HN3), Yongquan (KI1), Hegu ( LI4). Keywords: Acupressure, Open Heart Surgery, Cardiac Surgical Procedures